Contribution of differential alteration in oxidative stress and anti-oxidation related molecular signals to toxicity difference between atrazine and its main metabolites in nematodes - Rong Zhou; Yue Yu; Huan Miao; Na Zhao; Yuanqing Bu; Houhu Zhang (Ecotoxicology and Environmental Safety, 2023)
As a widely used herbicide, atrazine and its two main metabolites of deethylatrazine (DEA) and deisopropylatrazine (DIA) pose an exposure risk for both human beings and animals in the environment. In this study, Caenorhabditis elegans was selected as an in vivo model to compare the toxicity between atrazine and its main metabolites. Upon exposure from the larval stage L1 to adult day 3, both DEA and DIA showed less toxicity on locomotion and reproduction compared with atrazine at concentration of 0.001, 0.01 0.1 and 1 mg/L for parental generation. In addition, exposure to DEA and DIA at concentration of 0.1 mg/L also induced less transgenerational toxicity on locomotion than exposure to atrazine for both parental generation and offspring of F1–F4. Accordingly, exposure to DEA and DIA caused less ROS production and alteration in the expression of some genes (mev-1, gas-1, and clk-1) governing oxidative stress compared to atrazine. Meanwhile, DEA and DIA lead to less increase in expression of superoxide dismutase genes (sod-2 and sod-3) and SOD-3::GFP than atrazine. Moreover, atrazine and its two main metabolites differentially activated the daf-16 encoding FOXO transcriptional factor in insulin signaling pathway during the control of downstream target of SOD-3. Overall, our results highlighted the important role of oxidative stress and anti-oxidation related molecular signals in mediating toxicity of atrazine, DEA and DIA, which provided a novel explanation for the different toxicity between atrazine and its main metabolites.